Resin tube

By reducing molecular strain in polyolefin resin tubes and adopting specific resin combinations, the problem of polyolefin resin lacking surface smoothness is solved, and the excellent performance and low-cost characteristics of ultrapure water pipes are achieved.

CN119895186APending Publication Date: 2025-04-25SEKISUI CHEMICAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380066018.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-27
Filing Date
2023-09-26
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Among the existing ultrapure water pipe materials, fluororesin such as polyvinylidene fluoride (PVDF) has disadvantages in terms of construction properties and cost. At the same time, polyolefin resins lack surface smoothness and cannot meet the strict requirements after the integration of semiconductor chips is improved.

Method used

By reducing the strain amount of molecules received by the polyolefin resin during tube molding, specific resin combinations and process methods are used, such as using high-density polyethylene and fluorine-based lubricants, and controlling the average coefficient of variation of the molecular strain through FT-IR measurement, to achieve the goal of surface roughness Ra of 0.25 μm or less.

Benefits of technology

The excellent surface smoothness of polyolefin resin tubes is achieved, the surface roughness requirements in SEMI F57-0314 standard is met, and the elution amount of metal and organic components is suppressed, thereby improving the performance of the pipe.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119895186A_ABST
    Figure CN119895186A_ABST
Patent Text Reader

Abstract

A resin tube (100) has a first layer (210) containing a polyolefin resin, the first layer (210) constituting an inner peripheral surface (s) of the resin tube (100), and the average coefficient of variation (CV) of molecular strain of the inner peripheral surface (s) measured by an evaluation method A is 0.12 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a resin pipe. Background Art

[0002] Conventionally, in the manufacture of precision equipment such as semiconductor devices and liquid crystal display devices, ultrapure water purified to an extremely high purity in a wet process such as cleaning is used.

[0003] The pipes that constitute the ultrapure water delivery line are required to have a high inner surface smoothness in order to minimize metal elution and prevent the growth of bacteria.

[0004] As a material for ultrapure water piping, a fluororesin that is chemically inert, has gas barrier properties, has very little elution in ultrapure water, and has high inner surface smoothness is used. For example, in Patent Document 1, as piping used in semiconductor manufacturing equipment, liquid crystal manufacturing equipment, etc., a fluororesin double tube in which a fluororesin is laminated into two layers is disclosed. In the piping shown in Patent Document 1, the inner layer tube is composed of a fluororesin having excellent corrosion resistance and chemical resistance (for example, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), tetrafluoroethylene-hexafluoropropylene copolymer (FEP) or tetrafluoroethylene-ethylene copolymer (ETFE)), and the outer layer tube is composed of a fluororesin that can inhibit gas permeation (for example, polyvinylidene fluoride (PVDF)). In addition, patent document 2 discloses a multilayer pipe for ultrapure water piping, which comprises: a first resin layer composed of fluororesin and in contact with ultrapure water, and a second resin layer composed of an air-impermeable resin and arranged on the outer peripheral surface of the first resin layer. In addition, a third resin layer is disclosed that is arranged on the outer peripheral surface of the second resin layer to protect the second resin layer, and polyethylene is used as the third resin layer.

[0005] Among the materials used in ultrapure water piping, polyvinylidene fluoride (PVDF) is used in the semiconductor field for all practical purposes as piping within ultrapure water production equipment and piping for transporting ultrapure water from ultrapure water production equipment to the point of use, becoming a technical standard in ultrapure water piping.

[0006] Recently, as the integration of semiconductor chips has increased, circuit patterns have become increasingly smaller, and the requirements for ultrapure water piping have become increasingly stringent. For example, the standard related to the quality of ultrapure water piping used in semiconductor manufacturing has been published as SEMI F75 and is updated every two years.

[0007] On the other hand, as general tap water pipes, in addition to the existing cast iron pipes or vinyl chloride pipes, polyethylene pipes with excellent characteristics such as shock resistance, flexibility, corrosion resistance, and lightness are also used. In particular, for high-density polyethylene, effective use of existing rigidity is sought to achieve high performance. In high-density polyethylene pipes, high-density polyethylene pipes with excellent surface smoothness are also developed for the purpose of reducing friction with internal fluids and preventing the adhesion of scale, etc. At present, the surface roughness Ra of the high-density polyethylene pipe with the best surface smoothness is 0.4μm. This excellent surface smoothness is achieved by improving the gel or mixing unevenness in the resin by improving the polymerization catalyst and process technology (Non-patent Document 1).

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent Application Publication No. 2004-299808

[0011] Patent Document 2: Japanese Patent Application Publication No. 2010-234576

[0012] Non-patent literature

[0013] Non-patent document 1: TOSOH Research & Technology Review Vol. 44 (2000), p. 63-67 Summary of the invention

[0014] Technical problem to be solved by the invention

[0015] Compared with other general pipes, fluororesin pipes such as PVDF are disadvantageous in terms of construction and cost. However, in the context of stricter quality requirements for ultrapure water pipes, fluororesin pipes have become the only option as pipes that meet the required water quality, and they strongly support the outstanding performance of the pipes in terms of construction and cost.

[0016] Against this background, the inventors have conducted research focusing on replacing the material of ultrapure water piping with polyolefin resin. However, as a material for ultrapure water pipes, polyolefin resins lack surface smoothness. Currently, the limit value of the surface smoothness of high-density polyethylene resin pipes is about 0.4 μm, far from the level of 0.25 μm or less (outer diameter OD less than 250 mm) specified by SEMI F57-0314.

[0017] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a resin tube which is a polyolefin-based resin tube and has excellent surface smoothness with a surface roughness Ra of 0.25 μm or less.

[0018] Technical means of solving problems

[0019] The inventors of the present invention have conducted intensive research and found that by reducing the molecular strain amount of a polyolefin resin during tube molding, a resin tube having excellent surface smoothness with a surface roughness Ra of 0.25 μm or less can be obtained. The present disclosure is based on these findings and is completed through further repeated research. That is, the present disclosure provides an invention in the form shown below.

[0020] The resin tube of the first embodiment is a resin tube having a first layer containing a polyolefin resin, wherein the first layer constitutes the inner peripheral surface of the tube, and the average coefficient of variation (CV) of molecular strain of the inner peripheral surface measured by evaluation method A is 0.12 or less.

[0021] [Evaluation Method A]

[0022] Step 1. Use a microtome to cut the first layer of the inner surface of the resin tube, and prepare a test piece for measurement according to the size of the test measurement unit. The size of the test piece for measurement is 10 μm to 100 μm in thickness. Four test pieces for measurement are prepared for one resin tube. When viewed from the extrusion direction of the resin tube, four test pieces for measurement are cut from the 0 o'clock, 3 o'clock, 6 o'clock, and 9 o'clock directions.

[0023] Step 2. Perform IR measurement of the test piece for measurement using FT-IR.

[0024] ○FT-IR measurement conditions

[0025] (1) Device used: Fourier transform infrared spectrometer

[0026] (2) Spectrum One (manufactured by Perkin Elmer)

[0027] (3) Measurement method: Polarization measurement / transmission method

[0028] (4) Type of light source: MIR (tungsten lamp for mid-infrared)

[0029] (5) Resolution: 4cm -1

[0030] (6) Measurement range: 4000~400cm -1

[0031] (7) Cumulative number of times: 10 times

[0032] (8) Polarizer used: Wire grid infrared polarizer (made by STJAPAN)

[0033] (9) Measurement direction: When the extrusion direction of the resin tube used as the test piece is set to 0°, the measurement is performed from 0° (180°), +45° (-135°), -45° (+135°), ±90°

[0034] Step 3. Based on the results of FT-IR measurement, read the peak intensity representing infrared dichroism, normalize it with the maximum value of the measurement results in the four directions measured in (9), and calculate the coefficient of variation.

[0035] Step 4. Step 3 is performed on a total of four test pieces for measurement prepared from the same tube in step 1, and the coefficients of variation calculated for each are averaged to obtain an average coefficient of variation (CV).

[0036] In this way, by manufacturing a resin tube having an average coefficient of variation (CV) of 0.12 or less, which is an indicator of molecular strain, it is possible to provide a resin tube having excellent surface smoothness of 0.25 μm or less.

[0037] The resin tube according to a second aspect is the resin tube according to the first aspect, wherein the polyolefin-based resin is high-density polyethylene.

[0038] This can suppress the elution of organic components into pure water.

[0039] The resin tube according to a third aspect is the resin tube according to the second aspect, wherein the molecular weight distribution of the high-density polyethylene is 20-80.

[0040] A resin tube according to a fourth aspect is the resin tube according to the first aspect, wherein the first layer contains a fluorine-based lubricant.

[0041] Thereby, good inner surface smoothness can be obtained.

[0042] The resin tube according to a fifth aspect is the resin tube according to the first aspect, wherein the content of the fluorine-based lubricant in the first layer is 0.01 to 0.75% by weight.

[0043] A resin tube according to a sixth aspect is the resin tube according to the first aspect, further comprising a second layer laminated on the outer side of the first layer.

[0044] For example, when a core material layer is provided as the second layer, the rigidity of the entire resin tube can be ensured. In addition, when a gas barrier layer is provided as the second layer, oxygen from the outer surface of the resin tube can be prevented from penetrating into the inner layer, thereby maintaining the strength of the resin tube itself.

[0045] The resin tube according to a seventh aspect is the resin tube according to the sixth aspect, wherein the thickness of the first layer is 0.3 mm or more.

[0046] The resin tube of the eighth embodiment is the resin tube of any one of the first to seventh embodiments, wherein the total amount of elution of aluminum, barium, boron, calcium, chromium, copper, iron, lead, lithium, magnesium, manganese, nickel, potassium, sodium, strontium and zinc measured based on SEMI F57-0314 is 14 μg / m 2 the following.

[0047] This can suppress the elution of metal components into pure water.

[0048] The resin tube of the ninth aspect is the resin tube of any one of the first to seventh aspects, wherein the amount of calcium elution measured based on SEMI F57-0314 is 7 μg / m 2 Below, the elution amount of copper is 0.5μg / m 2 Below, the sodium elution amount is 1.5μg / m 2 Below, and zinc elution is 0.5μg / m 2 the following.

[0049] This can suppress the elution of calcium, copper, sodium, and zinc into pure water.

[0050] The resin tube of the tenth aspect is the resin tube of any one of the first to seventh aspects, wherein the elution amount of fluoride ions measured in accordance with SEMI F57-0314 is 600 μg / m 2 the following.

[0051] This can suppress the elution of fluoride ions into pure water.

[0052] The resin tube of the eleventh embodiment is the resin tube of any one of the first to seventh embodiments, wherein the elution amount of all organic components measured in accordance with SEMI F57-0314 is 10000 μg / m 2 the following.

[0053] This can suppress the elution of organic components into pure water.

[0054] Effects of the Invention

[0055] According to the present invention, it is possible to provide a resin tube using a polyolefin resin and having excellent surface smoothness with a surface roughness Ra of 0.25 μm or less. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 is a schematic cross-sectional view showing an example of the resin tube of the present disclosure.

[0057] Figure 2 is a schematic cross-sectional view showing another example of the resin tube of the present disclosure.

[0058] Figure 3: is a schematic cross-sectional view showing still another example of the resin tube of the present disclosure.

[0059] Figure 4 It is a perspective view showing an example of the resin tube of the present disclosure.

[0060] Figure 5 This is a diagram for explaining a method of obtaining a test piece for measuring the strain for evaluating the first layer of the present disclosure.

[0061] Figure 6 (a) and (b) are diagrams for explaining the measurement direction of the test piece of the present disclosure.

[0062] Figure 7 This is a diagram showing a graph in which the average coefficient of variation (CV) of Examples 1 to 8 and Comparative Examples 1 and 2 is plotted against the inner surface smoothness (Ra). DETAILED DESCRIPTION

[0063] Hereinafter, a resin tube according to an embodiment of the present disclosure will be described with reference to the drawings.

[0064] [1. Resin tube]

[0065] The resin tube of the present embodiment has a first layer including a polyolefin resin, the inner circumferential surface of the first layer constitutes the inner circumferential surface of the resin tube, and the surface roughness of the inner circumferential surface is less than 0.25 μm. The resin tube of the present embodiment is used, for example, to transport ultrapure water. The resin tube of the present embodiment is described in detail below. It should be noted that in this specification, the numerical range represented by "~" includes the values ​​at both ends. For example, the expression 0.5 to 3.0 mm means greater than 0.5 mm and less than 3.0 mm.

[0066] [1-1. Layer structure]

[0067] The resin tube of the present embodiment has a first layer containing a polyolefin-based resin. Figure 1 to Figure 3 An example of the resin tube according to the present embodiment will be given.

[0068] Figure 1 The resin tube 100 shown is composed of a single layer of a first layer 210 including a polyolefin-based resin. Figure 2 and Figure 3 The resin tubes 100a and 100b shown are examples of a multilayer structure in which another layer (an example of a second layer) is laminated on the outer surface of the first layer 210. In either case, the inner peripheral surface s of the first layer 210 constitutes the inner peripheral surface of the ultrapure water pipe 100, 100a, 100b.

[0069] Specifically, Figure 2The resin tube 100a shown includes: a first layer 210 containing a polyolefin resin and a core material layer 220 (an example of a second layer) laminated on the outer peripheral surface side of the first layer 210. Specifically, Figure 3 The resin tube 100 b shown includes a first layer 210 containing a polyolefin resin, a core layer 220 (an example of a second layer) laminated on the outer peripheral surface of the first layer 210 , and a gas barrier layer 230 laminated on the outer peripheral surface of the core layer 220 .

[0070] It should be noted that in Figure 1 In the resin tube 100 shown in the figure, one or more layers other than the core material layer 220 (for example, a gas barrier layer, etc.) may be further laminated on the outer peripheral side of the first layer 210. Figure 2 and Figure 3 In the resin tubes 100a and 100b shown, one or more layers (eg, adhesive layer) may be further laminated between the first layer 210 and the core layer 220 , between the core layer 220 and the gas barrier layer 230 , and / or on the outer peripheral surface of the gas barrier layer 230 .

[0071] The outer diameter of the resin tube 100, 100a, 100b of the present embodiment is not particularly limited, but in SEMI F57-0314, the outer diameter (OD) required for the surface roughness of the inner circumferential surface to be 0.25 μm or less is less than 250 mm. More specifically, the outer diameter of the resin tube 100, 100a, 100b of the present embodiment is preferably 20 to 180 mm, more preferably 25 to 100 mm, further preferably 28 to 50 mm, further preferably 30 to 40 mm, and particularly preferably 30 to 35 mm.

[0072] The total thickness of the resin tubes 100 , 100 a , and 100 b of the present embodiment is not particularly limited, and is, for example, 2 mm to 5 mm, preferably 2.5 mm to 4 mm, and more preferably 3 mm to 3.5 mm.

[0073] [1-2. First layer]

[0074] The first layer 210 is an extrusion-molded layer of a resin composition containing a polyolefin resin and a fluorine-based lubricant. Examples of the polyolefin resin include high-density polyethylene and polypropylene.

[0075] [1-2-1. High-density polyethylene]

[0076] High-density polyethylene (HDPE) refers to a polyethylene with a density (JIS6760) of 0.940 g / cm 3There is no particular upper limit on the density of the HDPE used in the first layer 210, and an example thereof is 0.970 g / cm 3 The following preferably includes 0.965 g / cm 3 Among the following, 0.960 g / cm 3 The following is more preferably 0.955 g / cm 3 The following is more preferably 0.950 g / cm 3 Among the following, 0.945 g / cm 3 the following.

[0077] Specific examples of the HDPE used in the first layer 210 include HDPE synthesized by polymerization using a chlorine-based catalyst such as a general-purpose Ziegler-Natta catalyst, and HDPE synthesized using a chromium-based catalyst or a metallocene catalyst.

[0078] The molecular weight of the HDPE resin used in the first layer 210 is not particularly limited, and for example, the weight average molecular weight Mw may be 1×10 5 ~10×10 5 From the viewpoint of suppressing the elution of organic components into pure water and / or further improving the surface smoothness, the weight average molecular weight Mw is preferably 3×10 5 ~10×10 5 , more preferably 4×10 5 ~9×10 5 , and more preferably 6×10 5 ~8.5×10 5 , and more preferably 7×10 5 ~8×10 5 , and 7.5×10 5 ~8×10 5 In the present invention, the weight average molecular weight Mw is a value measured in terms of polystyrene by gel permeation chromatography.

[0079] The molecular weight distribution (Mw / Mn) of the HDPE used in the first layer 210 is, for example, 20 to 80, preferably 40 to 80, more preferably 50 to 78, further preferably 60 to 76, further preferably 65 to 74, and particularly preferably 69 to 72. In the present embodiment, the molecular weight distribution (Mw / Mn) is a value (Mw / Mn) obtained by measuring the weight average molecular weight (Mw) and the number average molecular weight (Mn) converted to polystyrene by gel permeation chromatography and dividing Mw by Mn. It should be noted that the control of the molecular weight distribution (Mw / Mn) can be carried out by adjusting the amount of chlorine catalyst and / or the polymerization process (one-stage polymerization or multi-stage polymerization of more than two-stage polymerization). For example, by increasing the amount of chlorine catalyst, there is a tendency for the molecular weight distribution (Mw / Mn) to become larger, and by reducing the amount of chlorine catalyst, there is a tendency for the molecular weight distribution (Mw / Mn) to become smaller. Furthermore, by adopting multi-stage polymerization of two or more stages, the molecular weight distribution (Mw / Mn) can be increased, and by adopting one-stage polymerization, the molecular weight distribution (Mw / Mn) can be decreased.

[0080] In addition, as the calcium concentration in the first layer 210, for example, less than 15 ppb can be cited. From the viewpoint of further suppressing the amount of calcium eluted into pure water, as the calcium concentration in HDPE, preferably less than 12 ppb can be cited, and more preferably less than 10 ppb can be cited. The lower the calcium concentration, the less the amount of calcium eluted into pure water, so from this viewpoint, it is most preferably 0 ppm. On the other hand, the inner circumferential surface of the resin tube of the present embodiment has excellent smoothness, so even in the case where a chlorine catalyst such as a Ziegler-Natta catalyst (a catalyst for olefin polymerization prepared by mixing titanium tetrachloride or titanium trichloride with an organic aluminum compound [for example, triethylaluminum or methylaluminoxane, etc.]) is used in the synthesis of the HDPE used in the first layer 210 and a small amount of neutralizer is required, the elution of calcium into pure water can be effectively suppressed. It should be noted that the control of the calcium concentration in the first layer 210 is directly carried out by adjusting the amount of neutralizer added after the HDPE polymerization. Furthermore, since the amount of the neutralizing agent is affected by the amount of the chlorine-based catalyst, the calcium concentration can also be indirectly controlled by adjusting the amount of the chlorine-based catalyst.

[0081] The melt flow rate (MFR) of the HDPE used in the first layer 210 is not particularly limited, and for example, 5 to 20 g / 10 min. From the viewpoint of further improving the effect of suppressing the elution of impurities, the MFR of the HDPE used in the first layer 210 is preferably 9 to 15 g / 10 min, and more preferably 11 to 13 g / 10 min. It should be noted that in the present invention, the MFR is a value measured under the conditions of a temperature of 190° C. and a load of 21.6 kg as specified in JIS K-6922-2.

[0082] [1-2-2. Fluorine-based lubricants]

[0083] The fluorine-based lubricant used in this embodiment is a fluorine-containing polymer. Such a fluorine-containing polymer is usually a homopolymer or copolymer of a fluoroolefin having a fluorine atom to carbon atom ratio (F:C) of at least 1:2. Examples of the homopolymer include homopolymers of vinylidene fluoride and homopolymers of vinyl fluoride.

[0084] Examples of the copolymer include a copolymer of vinylidene fluoride and a fluorinated olefin having at least one terminal double bond and containing at least one fluorine atom on the double bond carbon atom. Specific examples of the fluorinated olefin as a comonomer from which the copolymer is derived include tetrafluoroethylene, chlorotrifluoroethylene, hexafluoropropylene, and pentafluoropropylene.

[0085] In this embodiment, as the fluorine-containing polymer used in the fluorine-based lubricant, one of the fluorine-containing polymers can be used alone, or multiple fluorine-containing polymers can be used in combination. In this embodiment, among the fluorine-containing polymers used in the fluorine-based lubricant, preferably a copolymer can be mentioned, and more preferably a vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer can be mentioned.

[0086] In the fluorine-based lubricant used in the present embodiment, it is also acceptable to further add an inorganic filler such as calcium carbonate, barium sulfate, talc and / or silica to the fluorine-containing polymer within a range that does not impair the target surface smoothness of the present invention.

[0087] The fluorine-based lubricant may be used alone or in combination. Among the fluorine-based lubricants, in the present embodiment, the fluorine-based lubricant preferably includes a lubricant that does not include an inorganic filler other than the fluorine-containing polymer (i.e., a fluorine-based lubricant that is 100% of the fluorine-containing polymer), and particularly preferably includes a lubricant that includes a vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer.

[0088] In the present embodiment, the content of the fluorine-based lubricant contained in the first layer 210 is not particularly limited as long as the effect of the present invention is not impaired. For example, 0.01 to 0.75% by weight may be cited. From the viewpoint of further improving the surface smoothness, 0.05 to 0.75% by weight may be cited preferably, 0.1 to 0.75% by weight may be cited more preferably, 0.2 to 0.75% by weight may be cited more preferably, and 0.25 to 0.75% by weight may be cited more preferably. In addition, from the viewpoint of improving the operability during extrusion molding, 0.01 to 0.7% by weight may be cited preferably, 0.01 to 0.65% by weight may be cited more preferably, 0.01 to 0.6% by weight may be cited more preferably, and 0.01 to 0.55% by weight may be cited more preferably.

[0089] [1-2-3. Surface roughness of inner peripheral surface s]

[0090] The surface roughness of the inner circumferential surface s of the first layer 210, i.e., the inner circumferential surface s of the resin tube 100, 100a, 100b of the present embodiment, is 0.25 μm or less. From the viewpoint of further reducing the total amount of elution of the main 16 metals (specifically, aluminum, barium, boron, calcium, chromium, copper, iron, lead, lithium, magnesium, manganese, nickel, potassium, sodium, strontium and zinc. Hereinafter, also referred to as "metals") and the elution amount of organic components, the surface roughness of the inner circumferential surface s is preferably 0.23 μm or less, more preferably 0.2 μm or less, further preferably 0.18 μm or less, and further preferably 0.16 μm or less. It should be noted that in the present embodiment, the surface roughness refers to the arithmetic mean roughness Ra measured based on JIS B0601:2001.

[0091] The surface roughness of the inner surface s can be controlled by controlling the strain of the polyolefin resin forming the first layer 210. Specifically, as a method for improving the surface roughness of the inner surface s, increasing the amount of fluorine-based lubricant can be cited. The preferred amount of fluorine-based lubricant is as described in "2-2. Fluorine-based lubricant".

[0092] [1-2-4. Other ingredients]

[0093] The resin tube 100, 100a, 100b of the present embodiment allows the first layer 210 to further contain other components than those described above. Examples of other components include other resin components other than the polyolefin resin and other additives other than the fluorine-based lubricant.

[0094] The other resin components are not particularly limited, and examples thereof include one or more selected from polyolefin resins other than polyethylene (such as polypropylene), polyether methyl ketone, acetal resin, polyvinyl chloride, etc. In the first layer 210 used in the present embodiment, the proportion of the other resin components relative to the total amount of 100 parts by weight of polyethylene and other resin components may be, for example, 30 parts by weight or less, preferably 20 parts by weight or less, more preferably 10 parts by weight or less, further preferably 5 parts by weight or less, further preferably 1 part by weight or less, further preferably 0.1 parts by weight or less, and most preferably 0 parts by weight.

[0095] As other additives, antioxidants (e.g., phenolic antioxidants, phosphorus antioxidants, sulfur antioxidants, aromatic amine antioxidants, and lactone antioxidants) can be cited. Since the resin tubes 100, 100a, and 100b of this embodiment have excellent smoothness of the inner peripheral surface s, it is allowed to further contain an antioxidant in the first layer 210. However, from the viewpoint of further suppressing the elution of organic components into pure water, it is preferred that other additives such as antioxidants are not contained in the first layer 210.

[0096] [1-2-5.Thickness]

[0097] exist Figure 1 In the case of the resin tube 100 of a polyethylene single layer shown, the thickness of the first layer 210 (that is, the thickness of the resin tube 100 ) is the same as the total thickness described in the above “1-1. Layer Configuration”.

[0098] In addition, Figure 2 and Figure 3 In the case of the resin tubes 100a and 100b having the multilayer structure shown, the thickness of the first layer 210 is, for example, 0.1 to 5 mm, 0.1 to 1 mm, preferably 0.2 to 0.8 mm, and more preferably 0.4 to 0.6 mm.

[0099] [1-3. Core material layer]

[0100] exist Figure 2 , Figure 3 In the resin tubes 100a and 100b, Figure 1 Compared with the resin tube 100, the thickness of the first layer 210 is made thinner, and on the other hand, in order to ensure the rigidity of the entire tube, a core material layer 220 is further laminated.

[0101] The core material layer 220 is an extrusion molding layer of any resin composition. From the viewpoint of adhesion to the first layer 210, as a preferred example of the resin used in the core material layer 220, polyolefin resins can be cited. As polyolefin resins, there is no particular limitation, as long as it is a polymer containing monomer units derived from olefins. As examples of polyolefin resins, polyethylene resins, ethylene-carboxylic acid alkenyl ester copolymer resins, ethylene-α-olefin copolymer resins, polypropylene resins, polybutene resins, poly (4-methyl-1-pentene) resins, etc. can be cited. These polyolefin resins can be used alone or in combination of two or more. Among these polyolefin resins, polyethylene resins and polypropylene resins are preferred from the viewpoint of improving the strength of the resin tube as a whole. In addition, among polyethylene resins and polypropylene resins, polyethylene resins are more preferred from the viewpoints of suppressing the content of low molecular weight components and suppressing the elution of organic components into pure water.

[0102] The polyethylene resin is not particularly limited, and examples thereof include low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), medium-density polyethylene (MDPE), and high-density polyethylene (HDPE). Among them, high-density polyethylene (HDPE) is preferred from the viewpoint of suppressing the elution of organic components into pure water.

[0103] Examples of the alkenyl carboxylate in the ethylene-alkenyl carboxylate copolymer resin include vinyl acetate, vinyl propionate, vinyl butyrate, isopropenyl acetate, allyl acetate, and the like, and preferably vinyl acetate is used.

[0104] Examples of the ethylene-α-olefin copolymer include copolymers obtained by copolymerizing α-olefins such as propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene or 1-octene as a copolymer component at a ratio of about several mol % relative to ethylene.

[0105] The molecular weight of the polyolefin resin used in the core layer 220 is not particularly limited, but is preferably the same as that of the polyethylene used in the first layer 210 as the inner layer. Specifically, the molecular weight of the polyolefin resin used in the core layer 220 can be selected from the weight average molecular weights described in "1-2-1. High-density polyethylene". In addition, the weight average molecular weight of the polyolefin resin used in the core layer 220 can be 0.8 to 1.2 times the weight average molecular weight of the HDPE used in the first layer 210 as the inner layer, preferably 0.85 to 1 times, and more preferably 0.9 to 0.95 times.

[0106] The molecular weight distribution (Mw / Mn) of the polyolefin resin used in the core material layer 220 is not particularly limited, and is, for example, 25 to 60, more preferably 30 to 55, further preferably 35 to 48, and particularly preferably 40 to 43.

[0107] The MFR of the resin used in the core layer 220 is not particularly limited, but is preferably equal to the MFR of the HDPE used in the first layer 210 as the inner layer. Specifically, the MFR of the resin used in the core layer 220 can be selected from the MFRs described in "1-2-1. High-density polyethylene". In addition, the weight average molecular weight of the polyolefin resin used in the core layer 220 can be 0.8 to 1.2 times, preferably 0.9 to 1.1 times, the weight average molecular weight of the HDPE used in the first layer 210 as the inner layer.

[0108] The calcium concentration in the core material layer 220 is not particularly limited, and a calcium concentration of a level contained in general-purpose grade resin is acceptable.

[0109] The core material layer 220 preferably contains an antioxidant. Examples of the antioxidant include phenolic antioxidants, phosphorus antioxidants, sulfur antioxidants, aromatic amine antioxidants, and lactone antioxidants. From the perspective of suppressing the influence of oxygen and ensuring the preferred strength, the content of the antioxidant in the core material layer 220 may be, for example, 0.01% by weight or more, preferably 0.1% by weight or more, and the upper limit of the content of the antioxidant may be, for example, 5% by weight or less, preferably 1% by weight or less, and more preferably 0.5% by weight or less.

[0110] The thickness of the core material layer 220 may be, for example, 1.5 mm or more, preferably 2 mm or more, and more preferably 2.3 mm or more, from the viewpoint of ensuring the rigidity of the resin tube itself. The upper limit of the thickness of the core material layer 220 may be, for example, 3.5 mm or less, preferably 3 mm or less, and more preferably 2.7 mm or less.

[0111] [1-4. Gas barrier layer]

[0112] Figure 3 The gas barrier layer 230 illustrated in the ultrapure water pipe 100b is provided on the outside of the core material layer 220. In addition, the gas barrier layer may also be provided on the outer surface of the core material layer 220. Figure 1 The outer side of the first layer 210 of the ultrapure water pipe 100 is provided. Figure 1 The gas barrier layer on the outside of the first layer 210 corresponds to an example of the first layer. The gas barrier layer prevents oxygen from the outer surface of the pipe from penetrating into the inner layer, so that the strength of the pipe itself can be well maintained. In addition, from the perspective of being able to well suppress the dissolution of gas in pure water, it is also preferable to provide a gas barrier layer. The gas barrier layer is preferably provided for the purpose of blocking oxygen.

[0113] The gas barrier layer is an extruded layer of a gas barrier resin composition. Examples of the gas barrier material include polyvinyl alcohol (PVA), ethylene-vinyl alcohol copolymer (EVOH), polyvinylidene chloride resin (PVDC) and polyacrylonitrile (PAN). Preferred examples include polyvinyl alcohol (PVA) and ethylene-vinyl alcohol copolymer (EVOH).

[0114] The thickness of the gas barrier layer 230 is, for example, 50 μm to 150 μm, and preferably 80 μm to 120 μm.

[0115] [1-5. Resin composition]

[0116] Regarding the polyethylene and fluorine-based lubricant contained in the first layer resin composition used in the first layer 210 comprising a polyolefin resin, and the composition of the polyethylene resin composition (the content or concentration of the components contained in the first layer resin composition), as described in “1-2. First layer” as the content or concentration of each component and the components contained in the first layer.

[0117] The high-density polyethylene used in the first layer resin composition can be synthesized by, for example, polymerization using a chlorine-based catalyst such as a general-purpose Ziegler-Natta catalyst, or can be synthesized using a chromium-based catalyst or a metallocene catalyst.

[0118] In a specific synthesis method of high-density polyethylene used in the first layer resin composition, a chlorine-based catalyst may be used for one-stage polymerization, and then a neutralizer (e.g., calcium stearate, hydrocalcite, etc.) may be added in an amount less than 15 ppb in terms of calcium concentration. In the case of adding a neutralizer in this way, one type of neutralizer may be used alone or in combination of multiple types. Alternatively, in other specific synthesis methods of high-density polyethylene used in the first layer resin composition, a chromium-based catalyst or a metallocene catalyst may be used for one-stage polymerization, excluding the addition of a neutralizer.

[0119] The first layer resin composition can be prepared by using the high-density polyethylene synthesized as described above or a commercially available product thereof and further blending a fluorine-based lubricant.

[0120] In addition, when the resin tube to be manufactured is a multi-layer structure including a core material layer 220, and when a polyolefin resin is used in the core material layer 220, in the specific synthesis method of the polyolefin resin, a chlorine catalyst can be used to carry out multi-stage polymerization (preferably two-stage polymerization), and then a neutralizer (such as calcium stearate, hydrocalcite, etc.) can be added in an amount converted to a calcium concentration of 15 to 25 ppb.

[0121] The core layer resin composition can be prepared by using the polyolefin resin synthesized as described above or a commercially available product thereof, and preferably further blending an antioxidant.

[0122] [1-6. Performance of Suppressing Elution of Impurities into Pure Water]

[0123] The resin tubes 100 , 100 a , and 100 b of the present embodiment have a highly smooth inner peripheral surface and thus are excellent in the performance of suppressing the elution of impurities into pure water.

[0124] In the impurity elution suppression performance of the resin tube of the present embodiment, regarding the metal elution suppression performance, the total amount of elution of the main 16 metals (referring to aluminum, barium, boron, calcium, chromium, copper, iron, lead, lithium, magnesium, manganese, nickel, potassium, sodium, strontium and zinc) measured based on SEMI F57-0314 (in this standard, refer to SEMI F40 standard) can be cited as 14μg / m 2 The following preferably includes 12 μg / m 2 The following is more preferably 10 μg / m 2 The following is more preferably 9 μg / m 2 The following is more preferably 8.5 μg / m 2 the following.

[0125] As a more specific example of the metal elution suppression performance, the elution amount of calcium measured according to SEMI F57-0314 is 7 μg / m 2 The following are preferably 6 μg / m 2 The following is more preferably 5.5 μg / m 2 As the elution amount of copper, for example, 0.5μg / m 2 The following preferably includes 0.45 μg / m 2 The following is more preferably 0.4 μg / m 2 As the elution amount of sodium, for example, 1.5μg / m 2 The following preferably includes 1.1 μg / m 2 The following is more preferably 0.7 μg / m 2 As the elution amount of zinc, for example, 0.5μg / m 2 The following preferably includes 0.3 μg / m 2 The following is more preferably 0.2 μg / m 2 the following.

[0126] In the impurity elution suppression performance of the resin tube of the present embodiment, regarding the anion elution amount, the elution amount of bromide ions is, for example, less than 10 μg / m 2 ; For example, the elution amount of fluoride ions is less than 1000 μg / m 2 , preferably less than 800 μg / m 2 , more preferably less than 700 μg / m 2 , and more preferably less than 600 μg / m 2 As nitrite ions, for example, less than 10 μg / m 2 As sulfate ions, for example, less than 10 μg / m 2 .

[0127] In the impurity elution suppression performance of the resin tube of the present embodiment, the organic component elution suppression performance can be exemplified by the elution amount of the total organic component (TOC) measured based on SEMI F57-0314, for example, 10000 μg / m 2 The following preferably includes 9000 μg / m 2 The following is more preferably 8500 μg / m 2 The following is more preferably 8000 μg / m 2 the following.

[0128] [1-7. Application]

[0129] The resin tube of this embodiment is used for conveying ultrapure water. Specifically, the resin tube of this embodiment can be used as piping in an ultrapure water production device, piping for conveying ultrapure water from an ultrapure water production device to a point of use, and piping for returning ultrapure water from a point of use.

[0130] The resin pipe of this embodiment is preferably used as a pipe for nuclear power generation water supply, which has particularly strict requirements on the quality of ultrapure water, or a pipe for transporting ultrapure water used in wet processing processes such as cleaning in the manufacturing process of pharmaceuticals, semiconductor elements or liquid crystals, and more preferably in the manufacturing process of semiconductor elements. As the semiconductor element, a semiconductor element with a higher degree of integration is also preferred, and specifically, it is more preferably used in the manufacturing process of semiconductor elements with a minimum line width of 65nm or less. As a standard related to the quality of ultrapure water used in semiconductor manufacturing, for example, SEMI F57-0314 can be cited.

[0131] Furthermore, the resin tube of the present embodiment is excellent in workability, and therefore, for example, welding work such as butt welding and EF (electrofusion) welding can be easily performed at a relatively low temperature.

[0132] [2. Method for manufacturing resin tube]

[0133] The resin tube of the present embodiment can be produced by extrusion-molding the first layer resin composition used for forming the first layer 210 .

[0134] (Important points during manufacturing)

[0135] When the resin is molded, it is subjected to various forces in the extruder, in the metal mold, and during the curing process, which causes strain. However, due to this strain, the smoothness of the inner surface deteriorates.

[0136] In order to achieve a surface roughness Ra of 0.25 μm or less as determined by SEMI F57-0314, it is important to reduce the strain to which the resin is subjected at all locations.

[0137] Specifically, the strain of the resin in the metal mold can be reduced by adding a fluorine-based lubricant. In addition, the deformation of the resin can be reduced by appropriately adjusting the amount of lubricant, the pulling speed, the draft, etc.

[0138] (Evaluation method of resin strain)

[0139] In the present embodiment, the strain of the resin of the resin tube is evaluated using the following evaluation method A. The evaluation method A is a method of quantifying the strain of molecules, that is, the amount of strain to which the resin is subjected during the manufacturing process.

[0140] Evaluation method A is a method designed based on a reference document, and can quantify the amount of molecular strain by evaluating the molecular orientation of the crystalline and amorphous parts of the polyolefin resin using FT-IR.

[0141] References: Paper title: Infrared dichroism and visible-ultraviolet dichroism studies on roller-drawn polypropylene and polyethylene sheets, Author name: A.Kaito, K.Nakayama&H.Kanetsuna, Pages 281-306|Received 15Sep 1986, Accepted 25Oct 1986, Published online: 14Dec 2006

[0142] The references are papers written on methods for evaluating the molecular orientation of polymers.

[0143] It is known that the CH bond in polyolefin molecules has multiple vibration modes, and each vibration is measured at a specific wave number (unit: cm -1 ) has an absorption peak. By measuring it, the molecular orientation state can be evaluated. It can be said that the smaller the molecular orientation, the smaller the strain on the resin.

[0144] (Evaluation Method A)

[0145] As step 1, the first layer 210 including the inner surface s of the resin tube 100, 100a, 100b is cut out using a microtome to prepare a test piece for measurement.

[0146] Figure 4 is a perspective view of the resin tube 100. Figure 4 As shown, the direction along the central axis of the resin tube 100 is defined as the axial direction A, the direction perpendicular to the central axis and close to or away from the central axis is defined as the radial direction B, and the direction rotating around the central axis A is defined as the circumferential direction C.

[0147] Figure 5 This is a diagram for explaining a method of obtaining a test piece for measurement. Figure 5 In the figure, a resin tube 100 is shown as an example. Figure 5 As shown, four test pieces 301, 302, 303, and 304 for measurement are prepared for one resin tube. The four test pieces 301, 302, 303, and 304 for measurement are cut out from the portion of the first layer 210 including the inner peripheral surface s in the directions of 0 o'clock, 3 o'clock, 6 o'clock, and 9 o'clock when viewed from the extrusion direction of the resin tube 100. The four test pieces 301, 302, 303, and 304 for measurement are each roughly rectangular. The extrusion direction of the resin tube 100 is a direction parallel to the axial direction A. The test piece 301 for measurement is the portion in the 0 o'clock direction when viewed from the extrusion direction of the resin tube 100. The test piece 302 for measurement is the portion in the 3 o'clock direction when viewed from the extrusion direction of the resin tube 100.

[0148] The measurement test piece 303 is a portion at the 6 o'clock direction when viewed from the extrusion direction of the resin tube 100. The measurement test piece 304 is a portion at the 9 o'clock direction when viewed from the extrusion direction of the resin tube 100. The four measurement test pieces 301, 302, 303, and 304 are of the same size. Figure 5 An enlarged view of the test piece 303 for measurement is shown. The thickness T is the length of the test piece 303 for measurement along the radial direction B. The width W is the length of the test piece 303 for measurement along the circumferential direction C. The length L is the length of the test piece 303 for measurement along the axial direction A. Specifically, the thickness T is 100 μm, the width W is 5 mm, and the length L is 40 mm. It should be noted that the size of the test piece for measurement can be appropriately changed according to the measurement unit of the device used, and from the perspective of detecting the peak intensity, the thickness T is preferably about 10 μm to 100 μm.

[0149] Next, as step 2, IR measurement of the test pieces 301, 302, 303, and 304 for measurement is performed using FT-IR.

[0150] ○FT-IR measurement conditions

[0151] (1) Device used: Fourier transform infrared spectrometer

[0152] (2) Spectrum One (manufactured by Perkin Elmer)

[0153] (3) Measurement method: Polarization measurement / transmission method

[0154] (4) Type of light source: MIR (tungsten lamp for mid-infrared)

[0155] (5) Resolution: 4cm -1

[0156] (6) Measurement range: 4000~400cm -1

[0157] (7) Cumulative number of times: 10 times

[0158] (8) Polarizer used: Wire grid infrared polarizer (made by STJAPAN)

[0159] (9) Measurement direction: When the extrusion direction of the resin tube used as the test piece for measurement is set to 0°, measurement is performed from 0° (180°), +45° (-135°), -45° (+135°), and ±90°.

[0160] Figure 6 (a) Yes Figure 5 An enlarged view of the test piece 303 for measurement is shown. Figure 6 (b) is a plan view of the test piece 303 for measurement. Figure 6 (a) and Figure 6 (b) is a diagram for explaining the measurement direction of FT-IR. The inner circumferential surface s of the test piece 303 for measurement is measured. The measurement direction 0° (180°) is a direction parallel to the axial direction A, and is represented by the measurement direction D1. The measurement directions ±90° are directions parallel to the axial direction A, and are represented by the measurement direction D2. The measurement direction D2 is a direction rotated 90° clockwise (90° counterclockwise) from the measurement direction D1 (refer to arrow E1). The measurement direction D2 corresponds to the circumferential direction C. The measurement direction D2 is Figure 6 (b) is parallel to the circumferential direction C. Clockwise rotation is indicated by positive, and counterclockwise rotation is indicated by negative. The measurement direction +45° (-135°) is indicated by the measurement direction D3. The measurement direction D3 is a direction rotated 45° clockwise (rotated 135° counterclockwise) from the measurement direction D1 (see arrow E2). The measurement direction -45° (+135°) is indicated by the measurement direction D4, which is a direction rotated -45° clockwise (rotated 135° counterclockwise) from the measurement direction D1 (see arrow E3).

[0161] Next, as step 3, based on the results of FT-IR measurement, the peak intensity indicating infrared dichroism is read, and the measurement results of the four directions measured in (9) are normalized by the maximum value to calculate the coefficient of variation. When the measurement values ​​of the four directions are set to α1, α2, α3, and α4, and the maximum value is set to α1, normalization is performed by, for example, calculating α1 / α1, α2 / α1, α3 / α1, and α4 / α1. The standard deviation and average value of these four values ​​are calculated, and the coefficient of variation is calculated by dividing the standard deviation by the average value.

[0162] Next, as step 4, step 3 is performed on other test pieces 301, 302, and 304 for measurement made from the same resin tube 100 in step 1, and the coefficient of variation is calculated respectively, thereby obtaining four coefficients of variation. By averaging these four coefficients of variation, an average coefficient of variation (CV) can be obtained. It should be noted that when the first layer 201 is formed of polyethylene, the wave number (cm2) of the peak read by the step of evaluation method A is -1 ) is 2019cm -1 In addition, when the first layer 201 is formed of polypropylene, it is preferably 809 cm -1 、1257cm -1 Nearby peaks.

[0163] In the present embodiment, by setting the average coefficient of variation (CV) to 0.12 or less, it is possible to obtain a resin tube having a surface smoothness with a surface roughness of 0.25 μm or less.

[0164] Example

[0165] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.

[0166] In the following Examples 1 to 8 and Comparative Examples 1 and 2, as shown in Table 1 below, the average coefficient of variation (CV) was determined using the evaluation method A for resin tubes produced by changing resin conditions, layer conditions, and molding conditions.

[0167] (Example 1)

[0168] In Example 1, Figure 2 The multilayer resin tube 100a of the structure shown in the figure. The resin forming the first layer 210 contains 99.7wt% of HDPF and 0.3% of lubricant. The lubricant uses a vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer. The extrusion amount of the resin during molding is set to 7.5kg / h, and the pulling speed of the resin is set to 0.49m / min. The resin tube 100a with a diameter of 25A after molding and a surface roughness Ra of the inner peripheral surface s of 0.15μm is prepared.

[0169] The resin tube 100a thus manufactured was read at 2019 cm using the evaluation method A. -1 The average coefficient of variation (CV) of the peaks below was calculated and the result was 0.03.

[0170] (Example 2)

[0171] The molding conditions of Example 2 are different from those of Example 1. In Example 2, the extrusion rate of the resin during molding is set to 50 kg / h, the pulling speed of the resin is set to 0.38 m / min, and the resin tube 100a having a diameter of 75A and a surface roughness Ra of the inner peripheral surface s of 0.15 μm after molding is prepared.

[0172] The resin tube 100a thus manufactured was read at 2019 cm using the evaluation method A. -1 The average coefficient of variation (CV) of the peaks below was calculated and the result was 0.11.

[0173] (Example 3)

[0174] The molding conditions of Example 3 are different from those of Example 1. In Example 3, the extrusion rate of the resin during molding is set to 30 kg / h, the pulling speed of the resin is set to 0.3 m / min, and the resin tube 100a having a diameter of 75A and a surface roughness Ra of the inner circumference s of 0.16 μm after molding is prepared.

[0175] The resin tube 100a thus manufactured was read at 2019 cm using the evaluation method A. -1 The average coefficient of variation (CV) was calculated for the peaks below, and the result was 0.09.

[0176] (Example 4)

[0177] In Example 4, Figure 1 The single-layer resin tube 100 of the structure shown in the figure. The resin forming the first layer 210 contains 99.7wt% of HDPF and 0.3% of lubricant. The lubricant is a vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer. The extrusion amount of the resin during molding is set to 24kg / h, and the pulling speed of the resin is set to 0.33m / min. The resin tube 100 with a diameter of 75A and a surface roughness Ra of the inner peripheral surface s after molding is prepared. 0.17μm.

[0178] The resin tube 100 thus produced was read at 2019 cm using the evaluation method A. -1 The average coefficient of variation (CV) of the peaks below was calculated and the result was 0.04.

[0179] (Example 5)

[0180] The molding conditions of Example 5 are different from those of Example 4. In Example 5, the extrusion rate of the resin during molding is set to 50 kg / h, the pulling speed of the resin is set to 0.64 m / min, and the resin tube 100 having a diameter of 75A and a surface roughness Ra of the inner peripheral surface s of 0.20 μm after molding is prepared.

[0181] The resin tube 100 thus produced was read at 2019 cm using the evaluation method A. -1 The average coefficient of variation (CV) of the peaks below was calculated and the result was 0.10.

[0182] (Example 6)

[0183] The molding conditions of Example 6 are different from those of Example 4. In Example 6, the extrusion rate of the resin during molding is set to 70 kg / h, the pulling speed of the resin is set to 0.5 m / min, and the resin tube 100 having a diameter of 75A and a surface roughness Ra of the inner peripheral surface s of 0.22 μm after molding is prepared.

[0184] The resin tube 100 thus produced was read at 2019 cm using the evaluation method A. -1 The average coefficient of variation (CV) of the peaks below was calculated and the result was 0.04.

[0185] (Example 7)

[0186] The molding conditions of Example 7 are different from those of Example 4. In Example 7, the extrusion rate of the resin during molding is set to 80 kg / h, the pulling speed of the resin is set to 0.28 m / min, and the resin tube 100 having a diameter of 150A and a surface roughness Ra of the inner peripheral surface s of 0.23 μm after molding is prepared.

[0187] The resin tube 100 thus produced was read at 2019 cm using the evaluation method A. -1 The average coefficient of variation (CV) was calculated for the peaks below, and the result was 0.05.

[0188] (Example 8)

[0189] In Example 8, a polypropylene molded article was used. The surface roughness Ra was 0.15 μm. The molded article thus prepared was read at 1257 cm using evaluation method A. -1 and 809cm -1 The peaks below were evaluated and the average coefficient of variation (CV) was calculated to be 0.07.

[0190] (Example 9)

[0191] In Example 9, a polypropylene molded article was used. The surface roughness Ra was 0.14 μm. The molded article thus prepared was read at 1257 cm using evaluation method A. -1 and 809cm -1 The peaks below were evaluated and the average coefficient of variation (CV) was calculated to be 0.05.

[0192] (Comparative Example 1)

[0193] The molding conditions of Comparative Example 1 are different from those of Example 4. In Comparative Example 1, the extrusion rate of the resin during molding is set to 50 kg / h, the pulling speed of the resin is set to 0.41 m / min, and a resin tube having a diameter of 75A and a surface roughness Ra of the inner peripheral surface s of 0.44 μm after molding is prepared.

[0194] The resin tube thus prepared was read using the evaluation method A at 2019 cm -1 The average coefficient of variation (CV) of the peaks below was calculated and the result was 0.15.

[0195] (Comparative Example 2)

[0196] In Comparative Example 2, Figure 2 The resin tube of the structure shown in the figure. The resin forming the first layer contains 100% HDPE and does not contain a lubricant. The extrusion amount of the resin during molding is set to 2.9kg / h, and the pulling speed of the resin is set to 0.16m / min. A resin tube with a diameter of 25A and a surface roughness Ra of the inner peripheral surface s after molding is prepared. 0.59μm.

[0197] The resin tube thus prepared was read using the evaluation method A at 2019 cm -1 The average coefficient of variation (CV) of the peaks below was calculated and the result was 0.19.

[0198] (Comparative Example 3)

[0199] In Comparative Example 3, a polypropylene molded article was used. The surface roughness Ra was 0.43 μm. The molded article thus prepared was read at 1257 cm using evaluation method A. -1 and 809cm -1 The peaks below were evaluated and the average coefficient of variation (CV) was calculated to be 0.17.

[0200] (Comparative Example 4)

[0201] In Comparative Example 4, a polypropylene molded article was used. The surface roughness Ra was 0.29 μm. The molded article thus prepared was read at 1257 cm using evaluation method A. -1 and 809cm -1 The peaks below were evaluated and the average coefficient of variation (CV) was calculated to be 0.49.

[0202] [Table 1]

[0203]

[0204] Figure 7This is a graph showing a graph of the average coefficient of variation (CV) plotted against the inner surface smoothness (Ra) for Examples 1 to 9 and Comparative Examples 1 to 4. Examples 1 to 7 and Comparative Examples 1 and 2 for polyethylene are plotted as ○, and Examples 8, 9 and Comparative Examples 3 and 4 for polypropylene are plotted as △. Figure 7 In the figure, the horizontal axis represents the inner surface smoothness (Ra) (μm), and the vertical axis represents the average coefficient of variation (CV).

[0205] As shown in the graph, it can be seen that when the average coefficient of variation (CV) is 0.12 or less, the inner surface smoothness (Ra) is 0.25 μm or less, and good inner surface smoothness can be obtained. Figure 7 In FIG. 1 , a straight line of CV=0.12 and a straight line of Ra=0.25 μm are indicated by dotted lines.

[0206] In addition, the total elution amount of 16 metals, the elution amount of TOC (Total Organic Carbon) and the elution amount of anions fully meet the SEMI F57-0314 standard as shown in Example 1. The material forming the first layer 210 is the same as that used in Examples 1 to 8, so Examples 2 to 8 also fully meet the SEMI F57-0314 standard as in Example 1.

[0207] Explanation of symbols

[0208] 100, 100a, 100b: Resin tube

[0209] 210: First floor

[0210] 220: Core layer

[0211] 230: Gas barrier layer

Claims

1. A resin tube having a first layer comprising a polyolefin resin, wherein: The first layer constitutes the inner peripheral surface of the resin tube, and the average coefficient of variation CV of the molecular strain of the inner peripheral surface measured by evaluation method A is 0.12 or less, [Evaluation Method A] Step 1. Use a slicer to cut the first layer of the inner surface of the resin tube, prepare a test piece for measurement according to the size of the test measurement unit, the size of the test piece for measurement is 10 μm to 100 μm in thickness, prepare 4 test pieces for measurement for one resin tube, observe from the extrusion direction of the resin tube, and cut out 4 test pieces for measurement from the 0 o'clock, 3 o'clock, 6 o'clock, and 9 o'clock directions; Step 2. Perform IR measurement of the test piece for measurement using FT-IR, ○FT-IR measurement conditions (1) Device used: Fourier transform infrared spectrometer (2) Spectrum One (manufactured by Perkin Elmer) (3) Measurement method: Polarization measurement / transmission method (4) Type of light source: MIR (tungsten lamp for mid-infrared) (5) Resolution: 4cm -1 (6) Measurement range: 4000~400cm -1 (7) Cumulative number of times: 10 times (8) Polarizer used: Wire grid infrared polarizer (made by STJAPAN) (9) Measurement direction: With the extrusion direction of the resin tube used to form the test piece being 0°, measurement was performed from 0° (180°), +45° (-135°), -45° (+135°), and ±90°; Step 3. Based on the results of the FT-IR measurement, read the peak intensity representing the infrared dichroism, normalize it with the maximum value of the measurement results in the four directions measured in (9), and calculate the coefficient of variation; Step 4. Step 3 is performed on a total of four test pieces for measurement prepared from the same resin tube in step 1, and the coefficients of variation calculated for each piece are averaged to obtain an average coefficient of variation (CV).

2. The resin tube according to claim 1, wherein The polyolefin resin is high-density polyethylene.

3. The resin tube according to claim 2, wherein: The molecular weight distribution of the high-density polyethylene is 20-80.

4. The resin tube according to claim 1, wherein The first layer contains a fluorine-based lubricant.

5. The resin tube according to claim 4, wherein The content of the fluorine-based lubricant in the first layer is 0.01 to 0.75% by weight.

6. The resin tube according to claim 1, further comprising: A second layer is laminated on the outer side of the first layer.

7. The resin tube according to claim 6, wherein The first layer has a thickness of 0.3 mm or more.

8. The resin tube according to any one of claims 1 to 7, wherein The total elution amount of aluminum, barium, boron, calcium, chromium, copper, iron, lead, lithium, magnesium, manganese, nickel, potassium, sodium, strontium and zinc measured based on SEMI F57-0314 is 14 μg / m 2 the following.

9. The resin tube according to any one of claims 1 to 7, wherein The calcium elution amount determined based on SEMI F57-0314 is 7 μg / m 2 Below, the elution amount of copper is 0.5μg / m 2 Below, the sodium elution amount is 1.5μg / m 2 Below, and zinc elution is 0.5μg / m 2 the following.

10. The resin tube according to any one of claims 1 to 7, wherein The elution amount of fluoride ions measured based on SEMI F57-0314 is 600 μg / m 2 the following.

11. The resin tube according to any one of claims 1 to 7, wherein The elution amount of all organic components measured according to SEMI F57-0314 is 10000 μg / m 2 the following.

Citation Information

Patent Citations

  • Transport device

    JP2004299808A

  • Multilayer tube

    JP2010234576A